El P. Antonio Orbe: la gnosis y la teología prenicena - Ladaria, Luis F. (Revista española de teología, 2007)
Fr. Antonio Orbe (1917-2003) has been one of the greatest specialists of the twentieth century in Patristic theology, especially in the pre-Nicean period. The article is about some of the points that have aroused his interest during his extensive scientific career: the first speculations about the procession of the Verb; the anthropology of the ecclesiastical authors in contrast with the Gnostic ones; the truth of the incarnation in front of the scandal which supposed, for many people, the assumption of the flesh; the unction of Christ in the Jordan River for the sanctification of his flesh in order to his redeeming mission in favour of all the mankind.